Development of an aluminum/amorphous nano-SiO2 composite using powder metallurgy and hot extrusion processes. Issue 17 (1st December 2017) - Issa, Hasan Kaser; Taherizadeh, Aboozar; Maleki, Ali; Ghaei, Abbas
Abstract: Ceramic nanoparticle reinforced aluminum matrix composites usually exhibit superior mechanical properties when compared to monolithic materials, particularly in severe working conditions such as elevated temperatures. Aluminum matrix nano-composites (AMNCs) are widely used for structural applications in aerospace and automotive industries due to their low density and high strength to weight ratio. The aim of this research was to study the effect of SiO2 nanoparticles as the reinforcing phase on the mechanical properties of aluminum matrix composites. For this purpose, powder metallurgy and subsequent hot extrusion methods were used to prepare a reference sample and several Al-SiO2 nano-composite rods, containing 1, 2 and 3 wt% nano-silica. Some sample preparation procedures for the manufacturing process, involved mixing, compaction, sintering, preheating and hot extrusion. Mechanical properties of the developed composites were investigated by macro- and micro-hardness, density measurement, tensile, cold compression and hot compression tests. A scanning electron microscope and an optical microscope were used for microstructural analysis of the composite and monolithic samples before and after the hot extrusion process. Experimental tests on aluminum matrix composites reinforced with nano SiO2 particles revealed that adding just 1 wt% SiO2 nanoparticle increases both hardness and tensile strength by 41.8% and 24.8%, respectively. In addition, the mechanical properties were seen to decrease with increases in the SiO2 weight fraction. Density also decreased as the SiO2 weight fraction increased. It can therefore be said that based on the findings of this study, the SiO2 nanoparticle can be used as an effective reinforcing material for developing aluminum matrix nano-composites.